PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Abdul Wahab Syakrani; Rahmatul Jannah; Resa Delina; Rezki Amalia (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Problems with Islamic religious education in schools usually include several major obstacles, such as students' lack of understanding of religious material, low student motivation to learn, teachers who are unprofessional or do not have a background in Islamic religious education, and students' lack of practice of religious teachings in their daily lives. In addition, uninteresting teaching methods and inadequate facilities and infrastructure also hinder the effectiveness of Islamic religious education. These problems mean that the objectives of Islamic religious education, which focus on shaping students' noble character and faith, have not been optimally achieved in schools.